Manuel Botelho de Oliveira e o barroco moderado: uma leitura de Lira Sacra (1703) - Cruz, Erimar Wanderson da Cunha (2021)
Lira Sacra was, as the author himself points out, the result of years of work, having reached its final manuscript compilation in 1703. Unlike Música do Parnaso, which was published in life by the author, the work of sacred content remained unknown until 1869 and it would take more than a century from then on for a paleographic edition (1971) to emerge, and even more than thirty years for a literary edition (2005) and a definitive critical form based on his superstitious testimonies (2007). This scarce and relatively recent reception, conditioned a very limited number of critical incursions, limited almost exclusively to introductions and comments in the editions of the text and to rare studies (LÓPEZ, 1969; RODRIGUES-MOURA, 2007). The option for such a discreet utterance suggests a possible affinity with the alternative modality of 17th century expression identified from the invective of Tommaso Stigliani against Adone de Marino, named by Franco Croce (1966), moderate Baroque. In order to recognize the lines of cultural communication with which Manuel Botelho de Oliveira dialogues, an overview was articulated with the main tendencies of sacred Romanesque poetry since the 12th century, with a focus on the 16th century Portuguese manifestations, on the Aristotelian matrix precept of Castelvetro and on the intellectual and poetic production by Torquato Tasso. Based on these assumptions, an analysis of Lira Sacra's stylistic profile is developed, describing her vocabulary, stylistic procedures and thematic structuring in the light of contemporary literary tradition. The textual examination shows that the Bahian poet demonstrates, in this undertaking, a coherence between poetic scope and stylistic form, passing through different traditional references, taking advantage of themes, eloquent formulas, without being slavishly attached to any one of them. With a moderate, eclectic and creative position, more attentive to clarity than to wonder, in an organic, harmonic and balanced architecture, in which it is possible to outline narrative cycles, comprising much of the history of Mary, Jesus and the saints celebrated through the liturgical year.